UPAYA MEMPERBAIKI SKILL SPEAKS MELALUI BERMAIN PERAN SISWA KELAS VII H SEMESTER GENAP SMP NEGERI 2 AMBULU - Lilik Sholihatul Khoiriyah (IKIP PGRI Jember, 2018)
The purpose of this research is to know the role play can improve Speaks Skill class VII H SMP Negeri 2 Ambulu Even Semester of Lesson 2015/2016. This is shown by the courage of speaking students who are very lacking and learning achievement of students who are far from the minimum standard of mastery. Based on the results of research conducted shows that there has been increasing Skill Speaks by students through role play. The subjects were 36 students of class VII H C SMP N 1 Ambulu consisting of 16 men and 20 women. Each cycle is carried out through the stage of action planning, action execution, Observation (observation), and reflection and evaluation at the end of the cycle. Methods of data collection used are methods of observation, interviews, documentation, and tests. The analysis technique used in this research is descriptive qualitative analysis. This study is a classroom action research with 2 cycles. These improvements can be seen in the results of learning activities that increase from cycle I to cycle II. Student score of cycle I average 75.14 to 80.42 in cycle II. This increased 11.11%, the classical completeness value of cycle 1 and cycle 2 from 75.00% to 86.11%.